2021
DOI: 10.1111/jpc.15243
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: Probiotics for treating acute diarrhoea in children with dehydration

Abstract: Aim This study aimed to evaluate the effectiveness of probiotics in treating children with acute diarrhoea and dehydration. Methods Medline, EMBASE, and the Cochrane Library databases were searched for relevant studies and statistical analysis was performed. Results A total of 17 randomised controlled trials (RCTs) involving 2861 participants met the inclusion criteria. Compared with placebo, probiotics reduced the duration of diarrhoea (12 RCTs [15, 17], n = 1907, mean difference − 21.33 h, confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Probiotics showed an excellent safety profile, a substantial reduction in the length of diarrhea, a decrease in bowel frequency, and a shortening of hospital stays. 8,14,15 In this study, the overall mean age was 3.67 ±1.29 years, with 134 (53.2%) females and 118 (46.8%) males. Consistently, Ali R et al, 16 reported that the children had an average age of 24.3 months, with a variability of approximately ±18.65 months.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Probiotics showed an excellent safety profile, a substantial reduction in the length of diarrhea, a decrease in bowel frequency, and a shortening of hospital stays. 8,14,15 In this study, the overall mean age was 3.67 ±1.29 years, with 134 (53.2%) females and 118 (46.8%) males. Consistently, Ali R et al, 16 reported that the children had an average age of 24.3 months, with a variability of approximately ±18.65 months.…”
Section: Resultsmentioning
confidence: 64%
“…Probiotics' 8,20,21 Probiotics have been extensively researched during the past several years for the treatment of diarrheal illnesses in pediatric populations. [15][16][17][18]21 Thus, intestinal flora existing in the intestinal mucosal barrier interacts with immune cells to promote the health and welfare of the host when probiotic is delivered. Less invasiveness and improved effectiveness are its benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Sharif et al, (2017) were in the same line with these findings and noted that significant decrease in the frequency of diarrhea in the probiotic group after admission to the hospital. Dehydration accounts for the highest percentage and is one of the common complications of acute diarrhea Lin Wu & Zhan, (2021). It was found that the significant improvement was showed in the degree of dehydration on the second and third day in probiotic study group, where slightly less than two thirds of children in the probiotic study group presented with no dehydration on the second day compared to one third of those children in control group.…”
Section: Discussionmentioning
confidence: 95%
“…Two other meta‐analyses focused on probiotics and synbiotics used in children living in developed countries (18) or on probiotics used in dehydrated children (19). As the results were not reported based on a single probiotic strain (or their combination), data from these analyses were not interpretable for the purposes of this document.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2019, 4 meta-analyses focusing on the use of probiotics for the treatment of acute infectious diarrhea have been published (17)(18)(19)(20).…”
Section: Treatment Of Acute Gastroenteritismentioning
confidence: 99%